Yellows and corm rot in gladiolus: Incidence, identification and characterization of Fusarium oxysporum f. sp. gladioli - S. SRIRAM and N.K. CHANDRAN, NITIKA GUPTA*, PRABHA K., G.B. KADAM (Indian Phytopathology, 2016)
To unravel the etiology of the plants showing yellowing, epinasty and wilting morphological and molecular diagnostics was carried out. Colony morphology and microscopic examinations indicated the pathogen to be Fusarium sp. To elucidate the identity conclusively, polymerase chain reaction (PCR) amplification of genomic region was done using primers based on internal transcribed spacer (ITS) region and translation elongation factor (Tef) region. ITS region of the pathogen showed 100 percent similarity to Fusarium oxysporum species and analysis of Tef region helped to narrow down to Fusarium oxysporumf. sp. gladioli. Characterization by molecular techniques using PCR to amplify the ITS and TEF 1Ã¡ allows identifying organisms that cannot be distinguished morphologically and they can also help to understand the mechanisms of pathogenic variation and therefore, to develop effective management strategies.